A Novel Cyano-Bridged Heteronuclear Complex Exhibiting C-H⋯Ni Close Interaction: [Cd(C4H7N)2Ni(μ-CN)4]n - Kürkçüoǧlu, G.S.; Yeşilel, O.Z.; Çayli, I.; Büyuk̈güngör, O. (Elsevier Science BV, 2011)
The cyano-bridged heteronuclear polymeric complex, [Cd(pyr) 2Ni(μ-CN)4]n, 1 (pyr = 3-pyrroline or 2,5-dihydropyrrole), has been synthesized and characterized by FT-IR, Raman spectroscopy, thermal and elemental analyses. The crystal structure of 1 has been determined by X-ray single crystal diffraction. The complex crystallizes in orthorhombic system and space group Pmna. In 1, Ni(II) ion is coordinated by four cyano ligands, and the Cd(II) ion is coordinated by four bridging cyanide ligands and two trans pyr ligands. The coordination environment of the Cd(II) ion described as distorted octahedral geometry, whereas around the Ni(II) centre has square planar geometry. The crystallographic analysis reveals that the weak intermolecular C-H⋯Ni interaction was found to be hydrogen bonding interaction, resulting in a 3D framework. Vibration assignments were given for all the observed bands and the spectral feature also supported to the structure of polymeric complex. The decomposition reaction take places in the temperature range 30-700 °C in the static air atmosphere. © 2011 Elsevier B.V. All rights reserved.
Keywords: 3-Pyrroline,2,5-Dihydropyrrole; C-H⋯Ni Interaction; Crystal Structure Analysis; Cyano-Bridged Complex; FT-IR and Raman Spectra; Tetracyanonickelate(II) Complex